The Cytotoxicity Assessment of Grapefruit Peel Essential Oil and Its Effect on Frying Stability of Sunflower Oil - Ghania Kaanin-Boudraa; Fatiha Brahmi; Linda Grimaud; Mohamed Lamine Freidja; Ourdia-Nouara Kernou; Daniel Henrion; Samir Hadjal; Khodir Madani; Lila Boulekbache-Makhlouf (Journal of Nutrition and Food Security)
Background: Frying oil lipids are prone to oxidation, so aromatic plants and their essential oils (EOs) have been applied to prevent this process. This study aimed to incorporate the grapefruit (Citrus x paradisi) EO in sunflower frying oil to protect it against oxidation. Before enrichment, a cytotoxicity test was performed to determine the non-cytotoxic concentration of this EO. Methods: Cell viability was evaluated using the MTT-based cytotoxicity assay. Various EO concentrations (0.01-0.5 mg/ml) were added to cultured cells Human Umbilical Vein Endothelial Cells (HUVECs) and Human Stellar Hepatic Cell lines LX-2 (SCC064) and incubated for 24 and 48 h. The stability of sunflower oil during frying was assessed by determining several parameters including peroxide value, polar compounds, and free fatty acids. Results: The obtained IC50 values after 24 h were 0.276 and 0.200 mg/ml for LX-2 and HUVECs cells, respectively, and the results after 48 h were 0.269 and, 0.216 mg/ml, respectively. Following that, the appropriate concentration of EO was incorporated into the sunflower oil. An oxidation acceleration test demonstrated that the lowest concentration of EO provided the best oxidation resistance (14 h 59 min) comparatively to the unfortified sunflower oil (11 h 63 min). The stability of enriched oil polar compounds during repeated frying was also noticed. Conclusion: The incorporation of this EO into sunflower oil during a deep-frying process led to a significant increase in its oxidative stability; therefore, it can be used as a food additive.